Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbantuan Aplikasi Berbasis Website Wordwall.Net Dan e-LKPD Wizer.Me Terhadap Motivasi Belajar Siswa - Subagja, Lareka Bagus (Postulat : Jurnal Inovasi Pendidikan Matematika, 2022)
Student motivation is one of the factors that influence learning outcomes. Therefore the authors pay special attention to this by conducting research on student motivation. Especially in this modern era, students tend to feel bored more quickly following conventional learning which is still centered on the teacher. So that learning must be made as interesting as possible, in order to trigger students' interest in participating in learning. Therefore, the authors decided to carry out learning using the Problem Based Learning (PBL) model assisted by website-based application media in the form of wordwall.net learning games and wizer.me e-LKPD media to increase student learning motivation. The reason for using the two website-based applications is the suitability of the content contained in the application, so that it can be adapted to the characteristics of existing students, such as several types of games that students can choose from on the wordwall.net website, and during the learning process students tend to want to do something instant. , such as listening to material rather than writing material, inputting answers using a cellphone, and so on. These habits or desires can be overcome using the wizer.me application because there are several supporting features, such as video link input, image/photo input, voice recording input, writing answers directly using your finger on your cellphone (hand writing), and many more. This is also the background of the article entitled "The Effect of the Problem Based Learning (PBL) Learning Model assisted by the application based on the wordwall.net website and e-LKPD wizer.me on student learning motivation". Keyword : PBL, wordwall.net, wizer.me, motivasi belajar.